U.B.K. UNIVERSITETETS BØRNEPSYKOLOGISKE KLINIK: – glimt af en udvikling over 50 år. - Almstrup, Ole (Psyke & Logos, 2022)
The backgrounds for establishing The Child Guidance Clinic of University of Copenhagen in 1950 inspired by the American Child Guidance movement are described. Developments in the clinic up to the establishment of Institute of Clinical Psychology in 1968 coloured by the author’s personal recollections from his two years post graduate clinical internship. The significance of the university-clinic for the establishment of Danish clinical child psychology is mentioned.